Migrant networks and job search outcomes: Evidence from displaced workers - Tommaso Colussi (Queen Mary University of London, School of Economics and Finance, 2013)
This paper investigates how the job search outcomes of displaced migrants are affected by the labor market outcomes of past co-workers of the same nationality. For this exercise I use matched employer-employee micro data on the universe of private-sector employees in Italy between 1975 and 2001. The analysis shows that a 10 percentage point increase in the network employment rate raises the re-employment probability within 36 months after job loss by 5.7 percentage points. The paper also sheds light on the different mechanisms generating the social effect and it highlights the role of migrant networks in explaining immigrant segregation.
Keywords: J61; J63; 330; Migration; Job displacements; Networks